2022
DOI: 10.3390/ijerph19053070
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Cardiovascular Diseases, Obesity, and Diabetes among Migrants in the United Kingdom: A Systematic Review

Abstract: There has been little agreement on the role that socioeconomic factors play in the aetiology of cardiovascular diseases (CVDs), obesity, and diabetes among migrants in the United Kingdom (UK). We systematically reviewed the existing evidence on this association to contribute to filling this gap in the literature. Two reviewers were involved at each stage of the review process to ensure validity. We comprehensively searched through several electronic databases and grey literature sources to identify potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As summarised in recent reviews, the evidence for the association between socioeconomic factors and cardiovascular and cerebrovascular diseases remains uncertain, with causation being speculative. 39 40 In summary, the subgroup differences we found highlight the need for high quality studies on the association, specifically the improvement in the design of studies, greater geographical representation, and adequate control for confounding factors to fill the gaps in evidence.…”
Section: Discussionmentioning
confidence: 89%
“…As summarised in recent reviews, the evidence for the association between socioeconomic factors and cardiovascular and cerebrovascular diseases remains uncertain, with causation being speculative. 39 40 In summary, the subgroup differences we found highlight the need for high quality studies on the association, specifically the improvement in the design of studies, greater geographical representation, and adequate control for confounding factors to fill the gaps in evidence.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, it was suggested that more highly educated people were most aware of the causes and consequences than less educated participants, which concurs with findings from the CRM study conducted in Ghana (Aberman et al 2022) that reported the wealthy to be more likely to understand the causes and risks associated with the issue. Wealth is often associated with increased education, and both are very important factors that have been shown to influence lifestyle behaviours amongst different populations (Gissing et al 2017;Ismail et al 2022;.…”
Section: Discussionmentioning
confidence: 99%
“… 93 This change may introduce financial instability, which, in turn, results in heightened stress levels, contributing to their CVD risk. 94 Moreover, lower income levels can limit access to health care, creating barriers to affording health‐related expenses such as nutritious food and medication. 95 Additionally, migrants with lower SES may face reduced access to educational and employment opportunities, indirectly affecting CVD risk through limited health literacy and reduced access to stable employment and resources for managing cardiovascular health effectively.…”
Section: Mechanisms Underlying the Cvd Burden In M...mentioning
confidence: 99%